The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1542-2011.2012.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Falling Out: Authoritative Knowledge and Women's Experiences with Pelvic Organ Prolapse

Abstract: Introduction Despite the high prevalence of pelvic organ prolapse many women suffer in silence, lacking the language and opportunity to describe their condition. There are limited descriptions of women’s experiences with pelvic organ prolapse in the literature. This qualitative study addressed the knowledge and experience of women with pelvic organ prolapse. Methods Semi-structured interviews were conducted with 13 women who had been previously diagnosed with pelvic organ prolapse. Transcripts of the intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…Improved information about potential pelvic floor problems could help better prepare women to manage sPOP following vaginal birth. Sadly, several other studies have shown similar results as ours regarding miscommunication between women with pelvic floor injury and healthcare professionals [11,12,19,20]. Midwives, obstetricians and physiotherapists need to be aware of the discourse on these forums and take part in the dialogue in order to ensure professional support for these women.…”
Section: Discussionsupporting
confidence: 80%
“…Improved information about potential pelvic floor problems could help better prepare women to manage sPOP following vaginal birth. Sadly, several other studies have shown similar results as ours regarding miscommunication between women with pelvic floor injury and healthcare professionals [11,12,19,20]. Midwives, obstetricians and physiotherapists need to be aware of the discourse on these forums and take part in the dialogue in order to ensure professional support for these women.…”
Section: Discussionsupporting
confidence: 80%
“…We included a total of 17 studies that evaluated POPrelated experiences of a total of 497 women by using different methodologies and tools for data collection. The main characteristics of the included studies 4,5,7,8,12,16,[26][27][28][29][30][31][32][33][34][35][36] are presented in Table 1.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Pelvic floor disorders and their impact on women are addressed in different ways and women's awareness of this condition is widely variable. [3][4][5][6] While some women may not seek medical care or wait for several years before seeking medical care for POP, 7,8 some women only disclose relevant information when asked questions directly about their symptoms and their impact on the quality of life, which also appears highly variable. [9][10][11][12][13] The impact on individual patients but also on clinical practice and research is therefore highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…There are common risk factors for POP, including aging, pregnancy, vaginal birth, birth trauma, chronic increases intra-abdominal pressure (obesity, chronic constipation, chronic coughing, repetitive heavy lifting), menopause, estrogen deficiency, genetic factor, prior surgery, myopathy, collagen abnormalities, smoking and lifestyle [3,12,13]. In prior, studies have used of X2, t-test, liner and logistic regression to find relationship between prolapse stage and risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common condition among women [1,2]. POP can affect the women of all ages and is associated with functional problems of the pelvic floor [3].…”
Section: Introductionmentioning
confidence: 99%